Language policy in fake news handling within French and Indonesian digital media - Merry ANDRIANI; Akmal Putra Tama (Faculty of Communications Science, Dr. Soetomo University, 2024)
This research examines the language politics carried out in handling fake news discourse through French and Indonesian online media platforms. As the internet-based communication has grown significantly in number, variety, quality and speed, making it also ideal to the fake news spread, then it requires certain language policy strategies to mitigate their destructive effect. The data of this research uses archives of online media articles, and related government websites in recent years in both countries, to look for the most recent discussions which are related to the discourse of handling fake news. Government and media discourses related to this matter are also highlighted. All the data is classified and analysed using the conceptual framework of language politics from Robert L Cooper. Since the nature of the research delves with discourses, it will be crucial to consider the discourse analysis method that refers to the critical and post-structural paradigms. Consequently, interdiscursivity and intertextuality are used as the main tools in the methodology of data analysis. As the result of this study, it shows that solid and consistent legal instruments have positive implications for maintaining journalistic quality in fighting fake news. The fake news strategy is also found in the narratives made by the authorities, but the terminologies given are different from the lexical labels to the discourse of political opponents in the public sphere. France and Indonesia utilise distinct strategies in addressing online media fake news.